Case report: Therapy-related myeloid neoplasms in three pediatric cases with medulloblastoma - Mak, Li Shun; Li, Xiuling; Chan, Wilson Y. K.; Leung, Alex W. K.; Cheuk, Daniel K. L.; Yuen, Liz Y. P.; So, Jason C. C.; Ha, Shau Yin; Liu, Anthony P. Y. (Frontiers in Oncology, 2024)
Introduction: Medulloblastoma is the most common malignant brain tumor in children, often requiring intensive multimodal therapy, including chemotherapy with alkylating agents. However, therapyrelated complications, such as therapy-related myeloid neoplasms (t-MNs), can arise, particularly in patients with genetic predisposition syndromes. This case report presents three pediatric cases of medulloblastoma with subsequent development of t-MNs, highlighting the potential role of genetic predisposition and the importance of surveillance for hematological abnormalities in long-term survivors.Case Presentation: We describe three cases of pediatric medulloblastoma who developed t-MNs after receiving chemotherapy, including alkylating agents. Two of the patients had underlying genetic predisposition syndromes (TP53 pathologic variants). The latency period between initial diagnosis of medulloblastoma and the development of secondary cancer varied among the cases, ranging from 17 to 65 months. The three cases eventually succumbed from secondary malignancy, therapy-related complications and progression of primary disease, respectively.Conclusions: This report highlights the potential association between genetic predisposition syndromes and the development of therapy-related myeloid neoplasms in pediatric medulloblastoma survivors. It underscores the importance of surveillance for hematological abnormalities among such patients.